Avascular necrosis of humeral head after proximal humerus fracture: comparison between classification systems in predicting necrosis risk - Fazzari, Francesco; Canton, Gianluca; Giraldi, Gioia; Falcioni, Nicholas; Clocchiatti, Susanna; Rasio, Nicholas; Murena, Luigi (Acta Biomedica Atenei Parmensis, 2023)
Background and aim: Avascular necrosis (AVN) of the humeral head is a relatively frequent complication after proximal humerus fractures (PHF). There are many factors related to the risk of developing AVN, with fracture complexity being one of the most relevant. Aim of the present study is to evaluate the correlation between different classification systems and the risk of post-operative AVN in patients treated with locking plate fixation for Neer 3 and 4-part PHFs. Methods: The study population included 44 patients (F:M 2:1, mean age 62) treated between December 2014 and April 2019. Fractures were classified according to Neer, Russo and Lego classifications and Hertel’s criteria. AVN was established on postoperative radiographs after a minimum follow-up of 6 months. The odds ratio (OR) for AVN for each classification subtype was calculated.Results: The incidence of necrosis was 11%. Significant association with AVN was found for Neer 4 part (OR=8), Russo IVB (OR=4), Lego pattern 12 (OR=8) and in presence of 3 mayor Hertel’s criteria (OR=15,5).Conclusions: There is a significant association between AVN and Neer 4 part, Russo type IVB and Lego pattern 12 fractures. AVN risk is also significantly higher in presence of 3 major Hertel’s criteria.